Study of innovation activity dynamics in Russia’s federal districts - N. A. Gerasimenko (Вестник университета)
The dynamics of indicators of innovation activities of Russia’s federal districts over 2005– 2019 has been studied. During this period, there has been an increase in the number of organisations that carried out research activities, and also in the total domestic expenditure on research and development. The number of new production technologies and the volume of innovative products produced has increased, and the payback rate on research and development costs has risen in all regions. The trends of decreasing in the innovation activities of organisations and a significant reduction in the number of personnel employed in the field of research and development have been detected. The share of new products in the total volume of products shipped remains low. This situation requires national and regional authorities to take appropriate regulatory actions.